2002
DOI: 10.5194/angeo-20-13-2002
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the contamination of SuperDARN global convection maps by non-F-region backscatter

Abstract: Abstract. Global convection mapping using line-of-sight Doppler velocity data from the Super Dual Auroral Radar Network (SuperDARN) is now an accepted method of imaging high-latitude ionospheric convection. This mapping process requires that the flow measured by the radars is defined solely by the convection electric field. This is generally only true of radar backscatter from the ionospheric F-region. We investigate the extent to which the E-region and ground backscatter in the SuperDARN data set may be misid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 37 publications
2
45
0
Order By: Relevance
“…It clarifies the latitudinal extent of the high-speed flow around 70 • MLAT. While the total cross-cap potential remains virtually unchanged, the new procedure results in substantially higher local fitted velocities and a noticeable change in the configuration of equipotential lines at the mesoscale level, in agreement with Chisham and Pinnock (2002).…”
Section: Fitting Experimental Datasupporting
confidence: 72%
See 1 more Smart Citation
“…It clarifies the latitudinal extent of the high-speed flow around 70 • MLAT. While the total cross-cap potential remains virtually unchanged, the new procedure results in substantially higher local fitted velocities and a noticeable change in the configuration of equipotential lines at the mesoscale level, in agreement with Chisham and Pinnock (2002).…”
Section: Fitting Experimental Datasupporting
confidence: 72%
“…Application of the conventional FITACF procedures in this case leads to incorrect estimates of V , W and other parameters producing large fitting errors. Chisham and Pinnock (2002) showed that contamination from SS can considerably alter mesoscale features of the fitted convection pattern and developed a technique for eliminating SS and MS from range-velocity distribution of echoes based on empirical identification of HF propagation modes. A similar approach was applied by Ponomarenko et al (2007), who successfully removed most MS from the data by applying the Blanchard-Baker algorithm with extended empirical thresholds for W and |V |.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is inevitable that some ground scatter has been included in this survey. A more complete removal of ground scatter from the data set could be achieved [Chisham and Pinnock, 2002] by increasing the limits set for the identification of ground scatter from those used; however this would also lead to the unwanted removal of real ionospheric scatter. This would lead to fewer time series available for use (in fact considerably so) with a consequent increase in spectral uncertainty.…”
Section: Methodsmentioning
confidence: 99%
“…occasion, E region backscatter may also contaminate F region data sets which can lead to much smaller Doppler velocities observed by SuperDARN (Chisham and Pinnock, 2002;Makarevich, 2008Makarevich, , 2010Bahcivan et al, 2013).…”
Section: R a Makarevich And W A Bristow: Superdarn And Pfisr F Rementioning
confidence: 99%
“…In large part because of this expectation, various restrictions are often employed in CSR/ISR and CSR/LEO comparative studies such as velocity filtering and selection of uniform-flow events (e.g., Davies et al, 1999;Drayton et al, 2005;Gillies et al, 2009). The other related aspect is possible effects of ground and E region scatter, both of which can effectively suppress HF radar velocity significantly below the convection component (Davies et al, 1999;Chisham and Pinnock, 2002;Makarevitch et al, 2004). While standard criteria on coherent echo velocity, width, and range eliminate most of ground and E region echoes, additional restrictions have been shown to improve correlations with ISR measurements even further, from ∼ 0.7 linear correlations to ∼ 0.9 (Gillies et al, 2009).…”
Section: Irregularity and Convection Velocitiesmentioning
confidence: 99%